2010
DOI: 10.1097/mol.0b013e32833e13fd
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein apheresis

Abstract: Lipoprotein apheresis seems to be going through a growth spurt, presumably reflecting better implementation of treatment guidelines or a broadening of indications for its use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 28 publications
1
29
0
2
Order By: Relevance
“…This study compared retrospective events from the lipid-lowering phase with prospective events in the apheresis phase, with limitations inherent using such an approach. Nevertheless, it provides the best evidence yet that lowering of Lp(a) is beneficial [61]. If confirmed by further studies, it would fulfill Koch's second postulate for Lp(a).…”
Section: Koch's Postulate For Lp(a)supporting
confidence: 52%
“…This study compared retrospective events from the lipid-lowering phase with prospective events in the apheresis phase, with limitations inherent using such an approach. Nevertheless, it provides the best evidence yet that lowering of Lp(a) is beneficial [61]. If confirmed by further studies, it would fulfill Koch's second postulate for Lp(a).…”
Section: Koch's Postulate For Lp(a)supporting
confidence: 52%
“…LA involves the extracorporeal removal of LDL and lipoprotein from whole blood or plasma. The previous term for LA was 'LDL apheresis,' but this was considered inappropriate because the procedure removes not only LDL, but also chylomicron, VLDL, and lipoprotein (a) [4] . Recent advances in technology have allowed direct adsorption of these lipoproteins from the blood.…”
Section: Discussionmentioning
confidence: 99%
“…23 LDL apheresis significantly lowers LDL-C and is considered the standard of care for patients with HoFH. 24 This procedure reduces the risk of coronary heart disease in patients with heterozygous FH. 25 However, drawbacks of apheresis include limited availability, high cost, procedure duration, and the need to maintain adequate vascular access.…”
Section: Discussionmentioning
confidence: 99%
“…25 However, drawbacks of apheresis include limited availability, high cost, procedure duration, and the need to maintain adequate vascular access. 24 There are also no prospective randomized studies demonstrating improved survival with apheresis, and despite apheresis, HoFH patients still develop extensive aortic calcification. 26 Prospective studies in non-HoFH populations have consistently shown a significant reduction in cardiovascular events and total mortality when LDL-C is reduced by 24% to 30%.…”
Section: Discussionmentioning
confidence: 99%